Kadar Air Tanah Gambut pada Kedalaman Berbeda di Desa Rasau Jaya II Kecamatan Rasau Kabupaten Kubu Raya - Nusantara, Rossie Wiedya (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2023)
Peatland dynamics are influenced by fluctuations in surface water on a land which can affect the water content of peat soil. The main factors that influence peat soil water content include land type, peat maturity and land elevation which determines the ground water level. The aim of this research is to determine the water content of peat soil at depths of 0-30 cm and 30-60 cm. The study location is in Rasau Jaya II Village, Rasau Jaya District, Kubu Raya Regency, West Kalimantan Province. Sample points are located at 8 (eight) locations with 9 (nine) sample points each at depths of 0-30 cm and 30-60 cm. The types of land in sequence from boring point 1 to 8 are oil palm plantations, rubber-pineapple-fern plantations, pineapple-fern plantations, corn plantations, corn plantations, used corn bushes, used corn bushes and oil palm plantations. The results of the analysis of the average water content at a depth of 0-30 cm at locations 1 to 8 were respectively 397.4%, 346.68%, 624.32%, 416.83%, 651.84%, 560.77% , 661.95% and 352.36% while at a depth of 30-60 cm respectively 772.23%, 780.13%, 764.29%, 748.43%, 973.04%, 970.29%, 787.14%, 911.59%. Based on the results of this analysis, it is known that the water content in the top layer (0-30 cm) is lower than the bottom layer (30-60 cm) with a ratio of 15.9%-61.3%.